Knowledge of osteoporosis among men attending primary care clinic and the associated factors - Samsudin, Suhaiza; Mohd Hashim, Syahnaz; Nawi, Azmawati (2017)
Osteoporosis has frequently been regards as a disease of women only. However, men are also at risk of developing osteoporosis. We aimed to evaluate the knowledge of osteoporosis among men and its associated factors.